Engaging Bodhisattva Compassion in Pedagogical Aporias - Hoyt, Mei (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
In teaching culturally sensitive and difficult issues, tensions and interruptions may arise, and educators and students may retreat to their respective comfort zones to avoid conflict and suffering, a pedagogical aporia occurs. This article introduces and examines Bodhisattva compassion from the Buddhist tradition, which offers insights and wisdom in transforming unexamined emotional responses into healthy and nonviolent expressions and embodiment of difference and dissonance. By tracing the Chinese etymological history of the term compassion and its use in Buddhist literature, I argue that Bodhisattva compassion embodies 悲心, a somatic, but unattached and awakened responsive heartmind. Bodhisattva compassion recognizes and accepts the unavoidability of human suffering, but it also liberates us from the common assumption of fellow-feeling and pity subsumed in sorrow and suffering. Guided by the concepts of wisdom and transforming the mind in Buddhism, bodhisattva compassion focuses on lucid awareness of one’s responsive heartmind and skillful actions to engage suffering. Pedagogy enlightened by bodhisattva compassion has curricular and instructional implications. In the struggle of identity politics or for social justice, it is probably more critical to develop ethical and undifferentiated compassion pedagogy than wrestling with power dynamics in our teaching.